2019
DOI: 10.1177/1933719118792095
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Vasodilator-Stimulated Phosphoprotein Phosphorylation, Profilin-1, and Cofilin-1 in Accreta and Protection by DHA

Abstract: Accreta and gestational trophoblastic disease (ie, choriocarcinoma) are placental pathologies characterized by hyperproliferative and invasive trophoblasts. Cellular proliferation, migration, and invasion are heavily controlled by actin-binding protein (ABP)-mediated actin dynamics. The ABP vasodilator-stimulated phosphoprotein (VASP) carries key regulatory role. Profilin-1, cofilin-1, and VASP phosphorylated at Ser157 (pVASP-S157) and Ser239 (pVASP-S239) are ABPs that regulate actin polymerization and stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…In a study performed by Ali et al, it was observed that placenta accreta, a medical condition characterized by abnormal attachment of the placenta to the uterine wall, expresses higher levels of CFL-1 in comparison to normal placentation. Moreover, they observed that only CFL-1 had significantly increased levels in focal accreta [127].…”
Section: Cfl-1mentioning
confidence: 97%
See 3 more Smart Citations
“…In a study performed by Ali et al, it was observed that placenta accreta, a medical condition characterized by abnormal attachment of the placenta to the uterine wall, expresses higher levels of CFL-1 in comparison to normal placentation. Moreover, they observed that only CFL-1 had significantly increased levels in focal accreta [127].…”
Section: Cfl-1mentioning
confidence: 97%
“…CFL-1 belongs to the actin depolymerizing factor/cofilin family and is the most abundant and ubiquitous member of the family in all studied non-muscle cells and in embryonic muscle cells [124,125]. CFL-1 is crucial for cell survival, as its primary function is to bind and depolymerize filamentous F-actin and prevent the polymerization of monomeric G-actin into filamentous F-actin, resulting in dynamic rearrangement of the actin cytoskeleton [125][126][127].…”
Section: Cfl-1mentioning
confidence: 99%
See 2 more Smart Citations
“…We demonstrated that basal cell adhesion molecule (BCAM, involved in trophoblast proliferation, migration, and invasion; Liu et al, 2022) was significantly less abundant in endometrial EVs from obese women than in endometrial EVs from nonobese women (by a factor of 1.6 in the XIC analysis). Conversely, we found that cofilin-1 (COF1, which is involved in actin remodelling and dynamics; Ali et al, 2019) is significantly more abundant in endometrial EVs from obese women than in endometrial EVs from nonobese women (by a factor of 0.6 in the SC analysis). Since these seven proteins are differentially expressed in endometrial EVs from obese vs. nonobese women, they might be potential biomarkers of endometrial receptivity.…”
Section:  the Protein Content Of Evs Isolated From Human Endometria...mentioning
confidence: 78%